2016
DOI: 10.1515/nuka-2016-0051
|View full text |Cite
|
Sign up to set email alerts
|

Radon problems in mining and post-mining areas in Upper Silesia region, Poland

Abstract: The new basic safety standards (BSS) Directive 2013/59/Euratom [1] puts EU member states under an obligation to establish, amongst others, national radon action plans. In order to address the issue of long-term risks from radon exposures, it is important to identify areas where elevated levels of radon can be expected. One of the types of areas affected by an increased migration of radon and by the penetration of radon into buildings are areas in which industrial activity, for example, the exploitation of mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
(19 reference statements)
0
11
0
1
Order By: Relevance
“…Therefore, the population is inevitably exposed to permanent radon levels, which can significantly differ from dwelling to dwelling. Wysocka 15 reported that indoor radon concentrations in mining and post‐mining areas exceeded the value of 300 Bq/m 3 in 2% of dwellings, whereas Ivanova and Badulin 19 reported that 50% of residential buildings in former uranium areas were above this reference level. Recently, Pressyanov 20 reported that 74% of houses were above 300 Bq/m 3 in Yana District, Bulgaria.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the population is inevitably exposed to permanent radon levels, which can significantly differ from dwelling to dwelling. Wysocka 15 reported that indoor radon concentrations in mining and post‐mining areas exceeded the value of 300 Bq/m 3 in 2% of dwellings, whereas Ivanova and Badulin 19 reported that 50% of residential buildings in former uranium areas were above this reference level. Recently, Pressyanov 20 reported that 74% of houses were above 300 Bq/m 3 in Yana District, Bulgaria.…”
Section: Introductionmentioning
confidence: 99%
“…This process has been studied in the coal mining regions of Great Britain, Germany, Poland, Ukraine, etc. [ 20 , 21 , 22 , 23 ]. High concentrations of radon in soil air in all studies of similar areas in the UK, Germany, Poland, and Ukraine have been recorded.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, high indoor radon levels in dwellings were reported for this region (Gulan et al 2017 ). The main factors which influence the abilities of radon migration are the mining induced changes of rock body (exploitation of mineral resources); in such regions, radon may exceed 300 Bq/m 3 in about 2% of buildings (Wysocka 2016 ). In earlier survey, indoor radon concentrations were measured with CR-39 detectors in this building in heating season (winter-spring, 6 months) in offices 7 and 14 (Table 1 ) (Gulan et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%